2008
DOI: 10.1016/j.exphem.2007.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Rapid platelet turnover in WASP(−) mice correlates with increased ex vivo phagocytosis of opsonized WASP(−) platelets

Abstract: Objective-Our objective was to determine a mechanism for the thrombocytopenia of murine Wiskott-Aldrich syndrome (WAS).Materials and Methods-Consumption rates of WAS protein (WASP)( −) and wild-type (WT) platelets were measured by injection of 5-chloromethylfluorescein diacetate (CMFDA)-labeled platelets into WT or WASP(−) recipients, and by in vivo biotinylation. Platelet and reticulated platelet counts were performed using quantitative flow cytometry. Bone marrow megakaryocyte number and ploidy was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 58 publications
(66 reference statements)
8
79
1
Order By: Relevance
“…Therefore, we assessed platelet clearance in both WT and Cib1 Ϫ/Ϫ mice using an in vivo biotinylation technique. 21 As with platelet production, the percentage of platelets cleared was unaltered on Cib1 deletion ( Figure 1B; supplemental Figure 2). Increased platelet count, combined with normal platelet production and clearance, suggests that, in terms of platelet regulation, Cib1 Ϫ/Ϫ mice simply operate at a higher baseline than the WT.…”
mentioning
confidence: 99%
“…Therefore, we assessed platelet clearance in both WT and Cib1 Ϫ/Ϫ mice using an in vivo biotinylation technique. 21 As with platelet production, the percentage of platelets cleared was unaltered on Cib1 deletion ( Figure 1B; supplemental Figure 2). Increased platelet count, combined with normal platelet production and clearance, suggests that, in terms of platelet regulation, Cib1 Ϫ/Ϫ mice simply operate at a higher baseline than the WT.…”
mentioning
confidence: 99%
“…WASp is expressed exclusively in hematopoietic cells and has a key role in actin polymerization and reorganization of actin cytoskeleton. Studies on WASp-null mice and WAS patients demonstrated that defective platelets are cleared at a faster rate by macrophages [70][71][72]. Anti-platelet autoantibodies could contribute to this process [73].…”
Section: Reduced Platelet Lifespanmentioning
confidence: 99%
“…Total inactivation reproduces the thrombocytopenia, which is moderate to severe depending on the genetic background and the individual, although microcytosis is absent. [35][36][37] Mouse models of constitutional thrombocytopenia haematologica | 2016; 101 (8) 901 Absence of WASp resulted in ectopic platelet release. 37 By relaying the signalling induced by collagen I and favoring the migration of megakaryocytes to sinusoids, WASp plays a key role in preventing the premature release of platelets in the bone marrow compartment.…”
Section: 33mentioning
confidence: 99%
“…37 In addition, this model proved to be useful in showing that the increased platelet consumption resulted from both intrinsic platelet factors and extrinsic factors, due to an increased susceptibility of these mice to develop platelet antibodies with subsequent opsonization and phagocytosis of platelets. 35,36 The development of "knock-in" mouse models has allowed one to explore the mechanisms governing the activation and stability of WASp, including the important role of phosphorylation at the Y293 single site (the murine equivalent of the Y291 site in human WASp). This phosphorylation site is critically involved in the activation of WASp in numerous cellular responses including proliferation, phagocytosis and especially the assembly of adhesion and chemotaxis structures.…”
Section: 33mentioning
confidence: 99%